Comprehensive analysis of the forming zone and improvement of diameter reduction prediction in the dieless wire drawing process - Braatz, Merle; Bohlen, Jan; Ben Khalifa, Noomane (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
The main disadvantage of the dieless wire drawing process is the complex interdependence of the process parameters, which often leads to process instability. The objective of this paper is to integrate the analysis of material behaviour with process performance, thereby extending the range of applicability and enhancing process control. For this purpose, the forming zone and its length are investigated and evaluated in detail to identify stable process scenarios and to predict the occurrence of (non-)localised deformation and actual diameter reduction. It is found that elevated temperatures above about 0.6 times the melting temperature result in well localised deformation, whereas increasing the feeding speed or the reduction ratio increases the length of the forming zone. An equation is presented for calculating the length of the forming zone based on material properties and process settings. In addition, stable process conditions are given, including minimum forming zone lengths and maximum possible diameter reductions. Predictions of actual diameter reductions using different approaches are also presented.
Keywords: Plastic Deformation; Dieless Wire Drawing; Forming Zone; Hot Forming; Magnesium Alloy